Applications and enhancement strategies of ROS-based non-invasive therapies in cancer treatment - Qiuyan Guo; Yingnan Tang; Shengmei Wang; Xinhua Xia (Redox Biology)
Reactive oxygen species (ROS) play a crucial role in the pathogenesis of cancer. Non-invasive therapies that promote intracellular ROS generation, including photodynamic therapy (PDT), sonodynamic therapy (SDT), and chemodynamic therapy (CDT), have emerged as novel approaches for cancer treatment. These therapies directly kill tumor cells by generating ROS, and although they show great promise in tumor treatment, many challenges remain to be addressed in practical applications. Firstly, the inherent complexity of the tumor microenvironment (TME), such as hypoxia and elevated glutathione (GSH) levels, hinders ROS generation, thereby significantly diminishing the efficacy of ROS-based therapies. In addition, these therapies are influenced by their intrinsic mechanisms. To overcome these limitations, various nanoparticle (NP) systems have been developed to improve the therapeutic efficacy of non-invasive therapies against tumors. This review first summarizes the mechanisms of ROS generation for each non-invasive therapy and their current limitations, with a particular focus on the enhancement strategies for each therapy based on NP systems. Additionally, various strategies to modulate the TME are highlighted. These strategies aim to amplify ROS generation in non-invasive therapies and enhance their anti-tumor efficiency. Finally, the current challenges and possible solutions for the clinical translation of ROS-based non-invasive therapies are also discussed.